P388 Shear wave elastography predicts short-term response to induction therapy in patients with Crohn's disease. (30th January 2023) - Sagami, S; Morikubo, H; Miyatani, Y; Fukuda, T; Asonuma, K; Maeda, M; Yoko, Y; Karashima, R; Hojo, A; Nakano, M; Hibi, T; Kobayashi, T
Abstract: Background: Endoscopy has been used to assess the disease activity of Crohn's disease (CD) but may not be sufficient considering the transmural nature of its inflammation. Bowel ultrasonography (BUS) has been reported to reflect disease activity of CD and long-term outcomes. We performed a prospective study to determine whether BUS can predict short-term clinical response to induction therapy. Methods: Consecutive CD patients with active ulcers in endoscopy requiring induction therapy (Anti-TNF antibody, IL-12/23 p40 antibody, integrin inhibitor, prednisolone) were prospectively enrolled at a single center from October 2018 to July 2022. Short-term clinical response was defined by a reduction of Crohn's disease activity index > 70 at week 8. Ultrasonographic findings (bowel wall thickness (BWT), colour Doppler signal (CDS), and shear wave elastography (SWE) were recorded for the most severely affected segment at baseline, week 1, and 8 and compared between responders and non-responders. Results: Seventeen out of 29 patients were classified as responders at week 8. There was no difference in BWT and CDS at baseline, week 1, and 8 between responders and non-responders (Table 1). In contrast, responders had lower baseline SWE compared with non-responders (2.7±0.3 vs. 3.8±0.3, p=0.02). Adjusted by the prior exposure to biologics, the lower SWE at baseline was associated with clinical response at week 8 (adjusted odds ratio associated with 0.1 m/s increase: 0.9, p=0.018) (Table 2). SWE did not change over time regardless of response for 8 weeks. Conclusion: Lower intestinal wall stiffness as measured by SWE is an independent predictor of short-term clinical response.